Bacteria Isolated from Hospital Surface Contamination and their Antimicrobial Susceptibility Patterns at Muhimbili National Hospital, Dar es Salaam, Tanzania (Tanzania Medical Journal, 2022)
BackgroundAn estimated 20%-40% of hospital acquired infections (HAI) are attributed to cross infection through health care workers, the patients and the hospital environment. However, data on bacteria contaminating hospital surfaces and their antibiotic susceptibility patterns in Tanzania, after hospital routine cleaning is limited. Findings from this study conducted in a national hospital in Tanzania will enrich data on understanding the sources of HAI. The study aimed to determine proportion of bacteria isolated from hospital surfaces and their antimicrobial susceptibility patterns.MethodsA cross sectional study was conducted at Muhimbili National Hospital (MNH), Dar es Salaam from August to October 2020. A total of 271 surface samples were collected from MNH surgical wards and surgical intensive care unit after cleaning and changing of bedsheets. The samples were then inoculated on culture media and thereafter antimicrobial susceptibility test was done. Data was analyzed in Statistical Package for Social Sciences (SPSS) version 20.0. Frequencies and proportions of bacteria isolated and their antibiogram were determined.ResultsOut of the 271 surface swabs collected, 131/271(48.3%) yielded positive culture results. Swabs from bedsheets, bed-sides, door-handles and sink-tap were 112, 112, 29 and 18, respectively, and the positive yield was the highest (59) in bed-sheets. Gram-positive bacteria (GPB) were the most prevalent accounting for 69.5% (91/131). Gram-negative bacteria (GNB) isolated accounted for 30.5% (40/131). GBP resistance to different antibiotics such as azithromycin, clindamycin and vancomycin among others ranged from 16.9%-100%. GNB isolated were resistant to amoxicillin clavulanic acid, meropenem, cefotaxime and ceftazidime. The prevalence of Methicillin-resistant Staphylococcus aureus (MRSA) was 75%(12/16). Resistance of Coagulase Negative Staphylococci (CoNS) ranged from 16.7%- 87.5%. Extended Spectrum Beta Lactamase producing Enterobacteriaceae (ESBL-PE) accounted for 55.5% (5/9).ConclusionA high proportion of both gram positive and gram-negative bacteria were isolated from hospital surfaces. CoNS were the most common bacteria followed by P. aeruginosa and S. aureus. Of the GPB, the prevalence of MRSA and CoNS was high and more than half of the GNB were ESBL-PE. Most of the bacteria isolated showed MDR. The findings support the need for enhanced efforts for infection and prevention control in the local setting to combat antimicrobial resistance.